Incentives for collecting gaharu (fungal-infected wood of Aquilaria SPP, Thymelaeaceae) in East Kalimantan - Wollenberg, Eva Karoline (2001)
The economic importance of Gaharu is assessed in three villages on the Bahau River in north-central Borneo to gain insights about the incentives for harvesting and management of valuable non-timber forest product. Three indicators of economic value-level and proportion of income, returns to labor, and proportion of Gaharu collecting households per village - are used to demonstrate the multiple incentives that NTFP income can generate. The concept of incentives logic is developed as an analytical technique to show how economic values can be linked to incentives for different types of management actions. The article discusses how incentives from Gaharu income were most likely linked to the stake local people had in the resource, their preferences about which forest which forest product to harvest, and their willingness to engage in collective action. These incentives contributed to sustainability to the extent they induced actions that reduce threats to the resource. The article suggests that an understanding of the influence of economic incentives on people's resource management can be improved by recognizing three factors: the multiple incentives created by an income, the logical link of those incentives to a management action, and the influence of other socio-cultural and biophysical factors on management